LOCAL SOLUTION FOR A NONLINEAR DEGENERATE HEAT EQUATION - Quispe Méndez, Teófanes (2008)
In present work, we study the existence of the local solutions to the mixed problem for a type of nonlinear degenerate heat equation with a generalized Lewis function.